A highly-efficient blue-light excitable red phosphor: intramolecular π-stacking interactions in one dinuclear europium(iii) complex. Issue 7 (17th December 2015) - Wang, Zhengliang; Yang, Hui; He, Pei; He, Yonghui; Zhao, Jishou; Tang, Huaijun
Abstract : The europium(iii ) complex [Eu2 (2, 7-BTFDBC)(DBM)4 (Phen)2 ] with multiple T-shaped and parallel-displaced π-stacking interactions exhibits intense red emission under blue light excitation with high colour purity. Abstract : A series of ternary dinuclear europium(iii ) complexes [Eu2 (2, 7-BTFDBC)3− n (DBM)2 n (Phen)2 ] ( n = 0, 1, or 2) were synthesized by using 2, 7-bis(4′4′4′-trifluoro-1, 3-dioxobutyl)-(9-ethyl-9 H -carbazole) (2, 7-BTFDBC), dibenzoylmethane (DBM), 1, 10-phenanthroline (Phen) and europium(iii ) ions. All these complexes display a broad excitation band in the blue region and high intensity emission with high colour purity. The intensity of emission significantly increases with the increase of DBM in [Eu2 (2, 7-BTFDBC)3− n (DBM)2 n (Phen)2 ] ( n = 0, 1, or 2). The theoretical predictions of the molecular geometry and electronic absorption spectrum of [Eu2 (2, 7-BTFDBC)(DBM)4 (Phen)2 ] confirm that the pendant phenyl domains engage in multiple T-shaped and parallel-displaced π-stacking interactions with the coordination sphere of two europium(iii ) centers. Using [Eu2 (2, 7-BTFDBC)(DBM)4 (Phen)2 ] as a red phosphor, a single red LED has been obtained with a ∼460 nm-emitting GaN chip.